Associations between Unplanned Pregnancy, Low Social Support, Domestic Violence, and Intrapartum Complication, with Postpartum Depression: Meta Analysis - Aranti, Wulan Adis; Indrawati, Devi; Mulyani, Sri; Murti, Bhisma; Marsim, Etanaulia (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: The postpartum period is a period where the risk of depression and other mental disorders generally increases due to the physiological and psychosocial changes that occur. The aim of this study was to measure the relationship using the meta-analysis method of unplanned pregnancy, poor social support, domestic violence, complications during childbirth with the incidence of postpartum depression.. Subjects and Method: This research is a systematic review and meta-analysis. Article searches were carried out using PICO. Population: Postpartum women. Interventions: unplanned pregnancy, poor social support, domestic violence, and complications during childbirth. Comparison: planned pregnancy, good social support, no domestic violence, and no complications during childbirth. Outcome: Postpartum depression. The keywords used in the article search were